Oligodendrocyte development and the onset of myelination in the human fetal brain - Jakovcevski, Igor; Filipovic, Radmila; Mo, Zhicheng; Rakic, Sonja; Zecevic, Nada (Frontiers in Neuroanatomy, 2009)
Oligodendrocytes are cells that myelinate axons, providing saltatory conduction of action potentials and proper function of the central nervous system. Myelination begins prenatally in the human, and the sequence of oligodendrocyte development and the onset of myelination are not thoroughly investigated. This knowledge is important to better understand human diseases, such as periventricular leukomalacia, one of the leading causes of motor deficit in premature babies, and demyelinating disorders such as multiple sclerosis (MS). In this review we discuss the spatial and temporal progression of oligodendrocyte lineage characterized by the expression of specific markers and transcription factors in the human fetal brain from the early embryonic period (5 gestational weeks, gw) until midgestation (24 gw). Our in vitro evidence indicated that a subpopulation of human oligodendrocytes may have dorsal origin, from cortical radial glia cells, in addition to their ventral telencephalic origin. Furthermore, we demonstrated that the regulation of myelination in the human fetal brain includes positive and negative regulators. Chemokines, such as CXCL1, abundant in proliferative zones during brain development and in regions of remyelination in adult, are discussed in the view of their potential roles in stimulating oligodendrocyte development. Other signals are inhibitory and may include, but are not limited to, polysialic acid modification of the neural cell adhesion molecule on axons. Overall, important differences in temporal and spatial distribution and regulatory signals for oligodendrocyte differentiation exist between human and rodent brains. Those differences may underlie the unique susceptibility of humans to demyelinating diseases, such as MS.